The Development of Vaccines against SARS-CoV-2 Virus. An Overview (Global Journal of Medical Research, 2021)
The COVID-19 is a zoonotic disease and is caused by the SARS-CoV-2 virus. It is the type of coronavirus. The structural proteins of the virus include the spike (S) protein, membrane (M) protein, envelop protein (E), and nucleocapsid (N) protein. The replication of the virus utilizes all structural proteins. The infection of the host occurs due to the binding of the spike protein to the angiotensin-converting enzyme II (ACE II). It is a positive-sense single-stranded RNA virus belong to the family Coronavridae. The recent outbreak of this disease has caused a lethal pandemic. The previous knowledge of SARS-CoV has helped to develop a vaccine against SARS-CoV-2 also. The humoral and cell-mediated immune response is protective against this infection. The antibody response generated against the S protein, which is the most exposed protein of SARS-CoV, has been shown to protect from infection in mouse models. Multiple studies have shown that the antibodies generated against the N protein of SARS-CoV, are highly immunogenic and abundantly expressed protein during infections.
Keywords: SARS-CoV-2; COVID-19; vaccine; viral vector; coronaviru s; live attenuated virus; protein sub-unit; virus-like particles (VLP)